Intermediate of sulfide electrolyte, preparation method of intermediate, sulfide electrolyte and preparation method of sulfide electrolyte

By combining a media-free pulverizer and inert gas fine grinding with static electricity removal treatment, the problems of material inhomogeneity and impurity introduction in the preparation of sulfide electrolytes were solved, realizing the preparation of sulfide electrolytes with high efficiency and low cost, and improving ionic conductivity and mass production capacity.

CN119263219APending Publication Date: 2025-01-07SUPERIONIC SOLID ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310799260.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Existing methods for preparing sulfide electrolytes suffer from low preparation efficiency, high cost, material inhomogeneity, and the introduction of impurities, making it difficult to achieve mass production.

Method used

Sulfide electrolyte intermediates are prepared by fine grinding using a media-free pulverizer and inert gas, combined with static electricity removal treatment. The use of grinding media is avoided. Fine grinding is carried out by air jet mill or thin film gyratory mixer. The grinding pressure and static electricity removal steps are controlled to ensure particle uniformity and ionic conductivity.

Benefits of technology

It improves the ionic conductivity of sulfide electrolytes, reduces preparation costs, enables more efficient batch production and more uniform material distribution, and avoids the negative effects of grinding media loss and static electricity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0004316427750000011
    Figure HDA0004316427750000011
  • Figure HDA0004316427750000012
    Figure HDA0004316427750000012
Patent Text Reader

Abstract

The invention discloses an intermediate of a sulfide electrolyte, a preparation method of the intermediate, the sulfide electrolyte and a preparation method of the sulfide electrolyte, the fluidity of the intermediate is 30s / 50g-75s / 50g, the preparation method of the sulfide electrolyte is characterized in that the intermediate is sintered to obtain the sulfide electrolyte, the grain size and material distribution of the sulfide electrolyte intermediate are uniform, the grain size is relatively fine, and the sulfide electrolyte intermediate has relatively high fluidity. According to the method, the intermediate of the sulfide electrolyte is adopted to prepare the sulfide electrolyte, and the improvement proportion of the ionic conductivity of the sulfide electrolyte is relatively high.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to an intermediate of a sulfide electrolyte and a preparation method thereof, a sulfide electrolyte and a preparation method thereof. Background Art

[0002] In recent years, with the rapid popularization of electronic devices and electric vehicles, lithium-ion batteries, as a key power source device, have seen rapid development in related industries. With the improvement of the functions and performance of various devices, the market has put forward higher requirements for the high capacity, long cycle and safety of batteries. Currently, commercial lithium-ion batteries use liquid electrolytes for the conduction of lithium ions between the positive and negative electrodes. The problems of flammability, puncture and short circuit fire, and the large space occupied by liquid electrolytes in the battery still exist. Using inorganic solid electrolytes instead of liquid electrolytes can achieve higher battery energy density, simpler battery design and higher safety. Therefore, the design and synthesis of solid electrolytes are very important for the future development of batteries.

[0003] At present, inorganic solid electrolytes are mainly divided into two technical routes: oxide electrolytes and sulfide electrolytes. Among them, sulfide electrolytes have ionic conductivity comparable to that of liquid electrolytes and a lower Young's modulus, making them very suitable for use in all-solid-state batteries. However, the current synthesis and preparation methods of sulfide electrolytes include multiple ball millings and continuous manual crushing of the compacted raw materials caused by ball milling. However, the above method makes the preparation cost too high, time-consuming, and the process is relatively cumbersome. At the same time, there is also a lot of material loss caused by the adhesion of materials to the ball milling beads and the loss caused by the collision of ball milling beads.

[0004] There are some patents in the prior art that use a high-speed rotating crushing blade device to batch crush and sinter the raw materials of sulfide electrolyte to obtain sulfide electrolyte. This method has the risk of metal impurities being added to the electrolyte material, causing material denaturation and oxidation that affect the performance of the electrolyte; it also generates a lot of heat, and the uniformity of the raw materials and the sintered electrolyte is not guaranteed.

[0005] Some patents also use dispersion tanks and ultrasound to disperse and sinter sulfide electrolyte raw materials at low and high speeds to obtain sulfide electrolytes. Such methods have high energy consumption, high noise, and are not economical to scale up. In addition, they will introduce metal impurities into the raw materials, which can easily cause internal short circuits in the battery. Ultrasonic dispersion can also easily generate a large amount of static electricity, causing the powder to stick to the wall, affecting the uniformity of raw material mixing and the original ratio and yield of the raw materials.

[0006] Some patents use oscillating mills with grinding media to grind raw materials, which causes loss of grinding media, low yield caused by raw materials sticking to the grinding media, easy hardening of raw materials, and the need for repeated manual crushing. The uniformity of raw material dispersion and crushing effect have not been improved, and the uniformity of electrolyte after batch sintering cannot be guaranteed. The efficiency is low and it is time-consuming and labor-intensive, making it difficult to scale up the process and produce. Although the above three methods do not use ball milling for the synthesis of electrolytes, they still use other grinding media or moving parts.

[0007] In summary, there is no mature mass production method for sulfide electrolytes. Ball milling or other methods that use grinding media to crush raw materials have low production efficiency and high cost. In addition, large-scale ball milling mixing and crushing will cause powder compaction and insufficient contact between grinding media and materials, resulting in uneven mixing and insufficient crushing of raw materials, which leads to poor product performance and poor uniformity. Therefore, there is an urgent need for a pulverization method without the aid of grinding media to prepare sulfide electrolytes in an efficient, controllable and more uniform manner. Summary of the invention

[0008] In response to the above technical problems, the present application provides an intermediate of a sulfide electrolyte and a preparation method thereof, a sulfide electrolyte and a preparation method thereof, wherein the sulfide electrolyte is a sulfide electrolyte obtained by de-ball milling and separating from the ball milling medium, and the obtained sulfide electrolyte has a high improvement ratio in ionic conductivity.

[0009] The specific technical solutions of this application are as follows:

[0010] The present application provides a method for preparing an intermediate of a sulfide electrolyte, comprising:

[0011] S1. Mixing and crushing the raw materials to obtain powder;

[0012] S2. grinding the powder using an inert gas to obtain the intermediate;

[0013] Here, static electricity is removed in step S1 and / or S2.

[0014] Preferably, in the above-mentioned method, the fine grinding of the powder using an inert gas is performed by placing the powder into a medium-free pulverizer and introducing an inert gas to perform fine grinding to obtain an intermediate.

[0015] Preferably, for the method described above, the media-free pulverizer is a jet mill or a thin film gyratory mixer, preferably a jet mill; preferably, the grinding pressure is 0.1-1.0Mpa, preferably 0.2-0.7Mpa, and more preferably 0.2-0.4Mpa.

[0016] Preferably, in the above method, after static electricity removal, the absolute value of the ion equilibrium potential of the powder and the intermediate is less than 100V.

[0017] The present application also provides an intermediate of a sulfide electrolyte, which is obtained by the preparation method of the above intermediate.

[0018] Preferably, for the intermediate described above, the fluidity of the intermediate is 30s / 50g-75s / 50g; and / or

[0019] The angle of repose of the intermediate is 50°-31°; and / or

[0020] The collapse angle of the intermediate is 40°-10°; and / or

[0021] The difference angle of the intermediate is 8°-20°.

[0022] Preferably, for the intermediate described above, D50 and / or D90 of the intermediate is 0.1-40 μm.

[0023] Preferably, for the intermediate described above, in the X-ray powder diffraction pattern of the intermediate, the peak intensity relationship between the characteristic absorption peaks is: the characteristic peak intensity ratio at 30°±0.5° and 27°±0.5° is 0.2-1.0; the characteristic peak intensity ratio at 30°±0.5° and 31.2°±0.5° is 1-5, preferably 1.5-3.

[0024] The present application provides a method for preparing a sulfide electrolyte, which comprises: sintering the intermediate described above to obtain a sulfide electrolyte.

[0025] The present application provides a sulfide electrolyte, which is prepared by the above method for preparing a sulfide electrolyte.

[0026] Effects of the Invention

[0027] (1) The particle size and material distribution of the sulfide electrolyte intermediate prepared by the method of the present application are uniform, and the particles are fine, which is conducive to the subsequent sintering process, so that the conductivity of the sulfide electrolyte obtained by sintering is higher; the uniform material distribution can also make the sintered product closer to the designed element ratio, and there will be no deviation in the element ratio that leads to a decrease in conductivity.

[0028] (2) The high-pressure inert airflow in the media-free pulverizer causes the particles to collide with each other, avoiding the negative effect of heat generation. The output particle size can also be adjusted by grinding parameters, and the intermediate particle size distribution is more uniform. At the same time, the synthesis speed is fast and the efficiency is high. There will be no material loss due to raw material adhesion and no loss of the grinding medium itself, thus reducing the synthesis cost.

[0029] (3) The present application further combines the static electricity removal link to eliminate negative phenomena such as agglomeration and adhesion to the inner wall of the equipment caused by static electricity during the grinding process, improves the insufficient grinding of raw materials due to static electricity and the uneven distribution of raw materials caused by the different adsorption forces of static electricity on particles of different densities, thereby achieving a better sintering effect.

[0030] (4) The present application improves the problems of sulfide electrolyte raw materials being easy to compact and difficult to disperse and crush, and being easy to generate static electricity that affects the crushing effect. By replacing other grinding equipment in parallel, compared with conventional preparation methods, less equipment needs to be replaced, the operation process is simple, and it is easy to scale up the process and mass produce sulfide electrolytes; and it can also improve the batch stability and particle size uniformity of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] Figure 1 This is a schematic diagram of the X-ray powder diffraction of the sulfide electrolyte intermediate of Example 1.

[0032] Figure 2 This is a schematic diagram of the X-ray powder diffraction of the sulfide intermediate of Comparative Example 3. DETAILED DESCRIPTION

[0033] The present application is described in detail below in conjunction with the described embodiments. Although specific embodiments of the present application are shown, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present application and to enable the scope of the present application to be fully communicated to those skilled in the art.

[0034] It should be noted that certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that technicians may use different nouns to refer to the same component. This specification and claims do not use the difference in nouns as a way to distinguish components, but use the functional differences of components as the criterion for distinction. As mentioned throughout the specification and claims, "including" or "comprising" are open-ended terms and should be interpreted as "including but not limited to". The subsequent description of the specification is a preferred embodiment of the present application, but the description is based on the general principles of the specification and is not intended to limit the scope of the present application. The scope of protection of the present application shall be determined by the attached claims.

[0035] The present application provides a method for preparing an intermediate of a sulfide electrolyte, which comprises:

[0036] S1. Mixing and crushing the raw materials to obtain powder;

[0037] S2. grinding the powder using an inert gas to obtain the intermediate;

[0038] In this case, static electricity is removed in step S1 and / or step S2.

[0039] In the present application, the present application does not impose any restrictions on the raw materials for preparing the sulfide electrolyte, which can be the raw materials commonly used in the art, for example, Li2S, P2S5, LiX, MX (X = Cl, F, Br, I, OH, O, O2, N, etc.; M = Ge, Si, Ta, La, Zr, Te, Se, Sn, Sb, etc.) can be used to prepare the sulfide electrolyte Li 7-a (M b P 1-b )SX a (0<a≤2, 0≤b≤1); Li2S, P2S5, GeS2, MS, LiX (X=Cl, F, Br, I, OH, O, O2, N; M=Ge, Si, Ta, La, Zr, Te, Se, Sn, Sb, etc.) can also be used to synthesize Li 10+c M 1+c P 2-c S 12 (-1≤c≤2); Li2S, P2S5, SiS2, MS, LiX (X=Cl, F, Br, I, OH, O, O2, N, etc.; M=Ge, Si, Ta, La, Zr, Te, Se, Sn, Sb, etc.) can also be used to synthesize Li 21-e Si3M d P 3-d S 23 X e (0≤d≤3, 0≤e≤3); X and M may be multiple, or M and X may not be included.

[0040] In the present application, there is no limitation on the equipment used for crushing, and conventional equipment in the art may be used for crushing, such as an electric grinder, a dispersion tank, a rotary mill, a stirrer, a mixer, etc. However, no grinding media is used, and in the crushing step, the grinding fineness is 1 mm.

[0041] In the present application, there is no limitation on the equipment used for static electricity removal, and static electricity removal can be carried out using conventional equipment in the field, such as ion fans, ion wind rods, ion wind nozzles, ion wind guns, environmental static electricity removal equipment, and methods such as covering the surface of the equipment with static electricity removal coatings and grounding the equipment can be used to remove static electricity.

[0042] In some embodiments, the powder is finely ground using an inert gas by placing the powder in a medium-free grinder and introducing an inert gas for fine grinding to obtain an intermediate. In some embodiments, the medium-free grinder is a jet mill or a thin film rotary mixer, preferably a jet mill; preferably, the grinding pressure is 0.1-1.0 MPa, preferably 0.2-0.7 MPa.

[0043] For example, the grinding pressure may be 0.1 MPa, 0.2 MPa, 0.3 MPa, 0.4 MPa, 0.5 MPa, 0.6 MPa, 0.7 MPa, 0.8 MPa, 0.9 MPa, 1.0 MPa, etc.

[0044] If the crushing pressure is too high (for example, the grinding pressure is greater than 1.0MPa), the raw material crystal form will be destroyed more thoroughly, affecting the sintering effect, and the resulting electrolyte performance will be worse; if the crushing pressure is too low (for example, the grinding pressure is less than 0.1Mpa), the raw material particle size will be too large, the contact between the particles will be insufficient, and it will also affect the sintering effect, resulting in poor electrolyte performance.

[0045] The jet mill is a processing method that uses high-speed airflow to grind the surface of materials. It uses the high-speed rotating flow field generated by the airflow to make the materials rotate, collide and rub continuously in the airflow, thereby achieving the purpose of grinding. The jet mill has the advantages of high grinding efficiency, high grinding precision, and little damage to the material. It is widely used in fine grinding and ultrafine grinding of powder materials.

[0046] The thin film gyratory mixer utilizes the high-speed rotation of the container itself to form a super strong centrifugal force, so that the material impacts the inner wall to complete the crushing, and the material adheres to the inner wall to form a state similar to a powder / liquid film during the mixing and crushing process, such as the Japanese PRIMIX thin film high-speed mixer FILMIX model 56-L.

[0047] In the present application, there is no limitation on the type and amount of the inert gas, and the inert gas commonly used in the art may be used, such as dry argon, nitrogen, H2S gas or a mixture of several thereof, which does not react with the raw materials.

[0048] This application uses grinding media without grinding media, and removes static electricity from the equipment and powder, which can eliminate negative phenomena such as agglomeration and adhesion caused by static electricity during the grinding process, and can maintain the consistency and uniformity of particle morphology and particle size, thereby ensuring product quality and controllability.

[0049] In addition, when using a jet mill, the raw materials can be crushed by the agitation of the airflow, and fine grinding without media ball milling can be achieved.

[0050] In the present application, during fine grinding, the grinding fineness reaches below 10 μm.

[0051] In the application, static electricity removal is performed in the steps of mixing and crushing raw materials and / or finely grinding powders using an inert gas, which means that static electricity removal can be performed in the step of mixing and crushing raw materials, or in the step of finely grinding powders using an inert gas, or in both the step of mixing and crushing raw materials and the step of finely grinding powders using an inert gas, preferably static electricity removal is performed in the step of finely grinding powders using an inert gas, and further preferably static electricity removal is performed in both the step of mixing and crushing raw materials and the step of finely grinding powders using an inert gas.

[0052] In the present application, there is no limitation on the particle size of the crushed powder, as long as it can enter the medium-free pulverizer. Preferably, the particle size D90 of the crushed powder is 0.5-40 mm.

[0053] For example, the powder particle size D90 after crushing can be 0.5-40mm, 0.5-35mm, 0.5-30mm, 0.5-25mm, 0.5-20mm, 0.5-15mm, 0.5-10mm, 0.5-5mm, 0.5-1mm, 1-40mm, 1-35mm, 1-30mm, 1-25mm, 1-20mm, 1-15mm, 1-10mm, 1-5mm, 5-40mm, 5-35mm, 5-30mm, 5-25mm, 5-20mm m, 5-15mm, 5-10mm, 10-40mm, 10-35mm, 10-30mm, 10-25mm, 10-20mm, 10-15mm, 15-40mm, 15-35mm, 15-30mm, 15-2 5mm, 15-20mm, 20-40mm, 20-35mm, 20-30mm, 20-25mm, 25-40mm, 25-35mm, 25-30mm, 30-40mm, 30-35mm, 35-40mm, etc.

[0054] In some embodiments, after static electricity is removed, the absolute value of the ion equilibrium potential of the powder and the intermediate is less than 100V, preferably less than 35V.

[0055] For example, after static electricity removal, the ion balance of the powder and the intermediate can be 99V, 90V, 80V, 70V, 60V, 50V, 40V, 30V, 20V, 10V, etc.

[0056] In the present application, the absolute value of the ion equilibrium potential on the device surface is less than 200V.

[0057] In the present application, there is no limitation on the method for determining the ion balance, which can be determined according to conventional methods in the art. The ion balance in the present application is determined using an electrostatic tester, using an electrode probe to perform the test at a distance of 25 mm from the powder.

[0058] In the present application, static electricity removal means that static electricity removal can be completed within 3.0 seconds at a distance of 100 mm from the object to be destaticized.

[0059] In some embodiments, the method comprises: mixing and crushing the raw materials to obtain a powder; finely grinding the powder using an inert gas to obtain the intermediate; wherein, static electricity is removed in steps S1 and / or S2. In some embodiments, finely grinding the powder using an inert gas is to place the powder in a medium-free pulverizer and introduce an inert gas for fine grinding to obtain an intermediate. In some embodiments, the medium-free pulverizer is a jet mill or a thin film gyratory mixer, preferably a jet mill; the grinding pressure is 0.1-1.0Mpa, preferably 0.2-0.7Mpa, and more preferably 0.2-0.4Mpa. In some embodiments, static electricity is removed in the steps of mixing and crushing the raw materials and finely grinding the powder using an inert gas. In some embodiments, the intermediate is the intermediate involved above. In some embodiments, after static electricity removal, the absolute value of the ion equilibrium potential of the powder and the intermediate is less than 100V.

[0060] The present application adopts the method of preparing the intermediate without grinding media, which can reduce the logistics loss caused by the adhesion of raw materials on the grinding media and the loss of the grinding media itself, and the improvement ratio of the ionic conductivity of the sulfide electrolyte prepared by using the intermediate is greatly improved.

[0061] The present application provides an intermediate of a sulfide electrolyte, which is obtained by the intermediate preparation method described above, and the fluidity of the intermediate is 30s / 50g-75s / 50g.

[0062] The fluidity refers to the time required for a certain amount of powder to flow through a standard funnel with a specified aperture. The smaller the value, the better the powder fluidity. It is a process property of the powder.

[0063] In the present application, there is no restriction on the method for determining the fluidity of the intermediate, which can be determined by conventional methods in the art. In the present application, the method of GB / T 1482-2022 is used for determination.

[0064] For example, the fluidity of the intermediate can be 30s / 50g, 35s / 50g, 40s / 50g, 45s / 50g, 50s / 50g, 55s / 50g, 60s / 50g, 65s / 50g, 70s / 50g, 75s / 50g, etc.

[0065] In some embodiments, the intermediate has an angle of repose of 50° to 31°; and / or

[0066] The collapse angle of the powder is 40°-10°; and / or

[0067] The difference angle of the powder is 8°-20°.

[0068] For example, the angle of repose of the intermediate can be 50°, 49°, 48°, 47°, 46°, 45°, 44°, 43°, 42°, 41°, 40°, 39°, 38°, 37°, 36°, 35°, 34°, 33°, 32°, 31°, etc.;

[0069] The collapse angle of the intermediate can be 40°, 39°, 38°, 37°, 36°, 35°, 34°, 33°, 32°, 31°, 30°, 29°, 28°, 27°, 26°, 25°, 24°, 23°, 22°, 21°, 20°, 19°, 18°, 17°, 16°, 15°, 14°, 13°, 12°, 11°, 10°, etc.;

[0070] The difference angle of the intermediate can be 8°, 9°, 10°, 11°, 12°, 13°, 14°, 15°, 16°, 17°, 18°, 19°, 20°, etc.

[0071] The angle of repose, also known as the angle of repose, refers to the angle between the free surface of the accumulated powder and the horizontal plane in a static equilibrium state. It is measured by making the powder fall naturally onto a specific platform to form a cone in a specific way. The size of the angle of repose directly reflects the fluidity of the powder. The smaller the angle of repose, the better the fluidity of the powder.

[0072] In the present application, the measurement may be performed using conventional methods in the art, for example, using the national standard GB / T 16913-2008 for measurement.

[0073] The collapse angle refers to the angle between the surface of the accumulated powder and the horizontal plane after the collapse when the accumulated powder is impacted by a certain external force and the free surface of the accumulated powder will collapse.

[0074] In the present application, the method for measuring the collapse angle is not limited in any way, and the collapse angle can be measured by conventional methods in the art, such as by using ASTM D6393-08.

[0075] The difference angle is the difference between the angle of repose and the angle of collapse. The larger the difference angle, the stronger the fluidity of the powder.

[0076] In the present application, the difference angle is measured by a conventional method in the art, for example, ASTM D6393-08 may be used for measurement.

[0077] In some embodiments, the D50 and / or D90 of the intermediate is 0.1-40 μm.

[0078] The present application does not impose any limitation on the determination method of D50 and D90, which can be determined by conventional methods in the art. For example, the German Sympatec laser particle size analyzer HELOS / BR-RODOS / L can be used to test the powder particle size.

[0079] For example, the D50 and / or D90 of the intermediate can be 0.1-40 μm, 0.1-30 μm, 0.1-20 μm, 0.1-10 μm, 0.1-5 μm, 0.1-1 μm, 0.1-0.5 μm, 0.5-40 μm, 0.5-30 μm, 0.5-20 μm, 0.5-10 μm, 0.5-5 μm, 0.5-1 μm, 5-40 μm, 5-30 μm, 5-20 μm, 5-10 μm, 10-40 μm, 10-30 μm, 10-20 μm, 20-40 μm, 20-30 μm, 30-40 μm, etc.

[0080] In the present application, the D50 and / or D90 of the intermediate being 0.1-40 μm means that the D50 of the intermediate is 0.1-40 μm or the D90 of the intermediate is 0.1-40 μm or both the D50 and D90 of the intermediate are 0.1-40 μm.

[0081] In some embodiments, the X-ray powder diffraction pattern of the intermediate has characteristic absorption peaks at diffraction angles 2θ of at least 27°±0.5°, 30°±0.5°, and 31.2°±0.5°. In some embodiments, the X-ray powder diffraction pattern of the intermediate is as follows Figure 1 shown.

[0082] In the present application, there is no limitation on the method for determining the X-ray powder diffraction pattern (XRD) of the intermediate, which can be determined by conventional methods in the art, such as XRD test conditions: 40 kV, 40 mA, Cu Kα, test range 5° to 85°, scanning speed 5° / min.

[0083] In this application, characteristic absorption peaks are defined using the following parameters: signal-to-noise ratio greater than 3, half-peak width less than 5°;

[0084] In the X-ray powder diffraction pattern of the intermediate, the peak intensity relationship between the characteristic absorption peaks is: the characteristic peak intensity ratio at 30°±0.5° and 27°±0.5° is 0.2-1.0; the characteristic peak intensity ratio at 30°±0.5° and 31.2°±0.5° is 1-5, preferably 1.5-3.

[0085] In the present application, the characteristic peak intensity ratio refers to the proportional relationship between the peak values ​​of two characteristic peaks. For example, for the characteristic peak intensity ratio at 30°±0.5° and 27°±0.5°, it refers to the proportional relationship between the peak value of the characteristic peak at 30°±0.5° and the peak value of the characteristic peak at 27°±0.5°.

[0086] For example, the ratio of the characteristic peak intensity at 30°±0.5° to 27°±0.5° can be 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, etc.;

[0087] The ratio of the characteristic peak intensities at 30°±0.5° and 31.2°±0.5° can be 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, etc.

[0088] In some embodiments, the fluidity of the intermediate is 30s / 50g-75s / 50g. In some embodiments, the angle of repose of the intermediate is 50°-31°; and / or the collapse angle of the intermediate is 40°-10°; and / or the difference angle of the intermediate is 8°-20°. In some embodiments, the D50 and / or D90 of the intermediate is 0.1-40μm. In some embodiments, in the X-ray powder diffraction pattern of the intermediate, the peak intensity relationship between the characteristic absorption peaks is: the ratio of the characteristic peak intensity at 30°±0.5° and 27°±0.5° is 0.2-1.0; the ratio of the characteristic peak intensity at 30°±0.5° and 31.2°±0.5° is 1-5, preferably 1.5-3.

[0089] The sulfide electrolyte intermediate described in the present application has a certain fluidity, so that the ionic conductivity of the prepared sulfide electrolyte is greatly improved.

[0090] The present application provides a method for preparing a sulfide electrolyte, which comprises: sintering the intermediate described above to obtain a sulfide electrolyte.

[0091] Subsequent steps may also include:

[0092] S11. crushing the sulfide electrolyte powder to obtain crushed sulfide electrolyte powder;

[0093] S12. grinding the crushed sulfide electrolyte powder by using an inert gas to obtain a sulfide electrolyte;

[0094] Here, static electricity is removed in step S11 and / or S12.

[0095] In the present preparation process, the static electricity removal in the step of crushing the sulfide electrolyte powder and / or finely grinding the crushed sulfide electrolyte powder with an inert gas refers to the static electricity removal in the step of crushing the sulfide electrolyte powder, or the static electricity removal in the step of finely grinding the crushed sulfide electrolyte powder with an inert gas, or the static electricity removal in the step of crushing the sulfide electrolyte powder and the step of finely grinding the crushed sulfide electrolyte powder with an inert gas. It is preferred to remove static electricity in the step of finely grinding the crushed sulfide electrolyte powder with an inert gas, and it is further preferred to remove static electricity in the step of crushing the sulfide electrolyte powder and the step of finely grinding the crushed sulfide electrolyte powder with an inert gas. The static electricity removal in the method can make the collision of particles more complete, reduce agglomeration and wall adhesion, and make the product more uniform.

[0096] The method of finely grinding the crushed sulfide electrolyte powder by using an inert gas is to put the crushed sulfide electrolyte powder into a medium-free pulverizer and introduce an inert gas to finely grind the powder to obtain a sulfide electrolyte.

[0097] In some embodiments, the D50 and / or D90 of the finely ground sulfide electrolyte is 0.1-40 μm.

[0098] The D50 and / or D90 of the sulfide electrolyte may be 0.1-40 μm, 0.1-30 μm, 0.1-20 μm, 0.1-10 μm, 0.1-5 μm, 0.1-1 μm, 0.1-0.5 μm, 0.5-40 μm, 0.5-30 μm, 0.5-20 μm, 0.5-10 μm, 0.5-5 μm, 0.5-1 μm, 5-40 μm, 5-30 μm, 5-20 μm, 5-10 μm, 10-40 μm, 10-30 μm, 10-20 μm, 20-40 μm, 20-30 μm, 30-40 μm, etc.

[0099] The present application does not impose any restriction on the particle size of the crushed sulfide electrolyte powder, as long as it can enter the medium-free pulverizer. For example, the particle size D90 of the crushed sulfide electrolyte powder can be 0.5-40mm, 0.5-35mm, 0.5-30mm, 0.5-25mm, 0.5-20mm, 0.5-15mm, 0.5-10mm, 0.5-5mm, 0.5-1mm, 1-40mm, 1-35mm, 1-30mm, 1-25mm, 1-20mm, 1-15mm, 1-10mm, 1-5mm, 5-40mm , 5-35mm, 5-30mm, 5-25mm, 5-20mm, 5-15mm, 5-10mm, 10-40mm, 10-35mm, 10-30mm, 10-25mm, 10-20mm, 10-15mm, 15-40mm, 15-35mm , 15-30mm, 15-25mm, 15-20mm, 20-40mm, 20-35mm, 20-30mm, 20-25mm, 25-40mm, 25-35mm, 25-30mm, 30-40mm, 30-35mm, 35-40mm, etc.

[0100] In some embodiments, the medium-free pulverizer is a jet mill or a thin film rotary mixer, preferably a jet mill; preferably, the grinding pressure is 0.1-1.0 MPa, preferably 0.2-0.7 MPa, and more preferably 0.2-0.4 MPa.

[0101] For example, the grinding pressure may be 0.1 MPa, 0.2 MPa, 0.3 MPa, 0.4 MPa, 0.5 MPa, 0.6 MPa, 0.7 MPa, 0.8 MPa, 0.9 MPa, 1.0 MPa, or the like.

[0102] In some embodiments, after static electricity removal, the absolute value of the ion equilibrium potential of the crushed sulfide electrolyte powder and the sulfide electrolyte is less than 100V; preferably, the absolute value of the ion equilibrium potential on the surface of the device is less than 200V.

[0103] For example, after static electricity removal, the ion balance of the crushed sulfide electrolyte powder and the sulfide electrolyte can be 99V, 90V, 80V, 70V, 60V, 50V, 40V, 30V, 20V, 10V, etc.

[0104] The present application adopts the method described to prepare sulfide electrolyte. Since no grinding media is used in the preparation process, the production speed is fast and the efficiency is high. In addition, through the intervention of the static electricity removal step, the agglomeration of powders during the grinding process and the adhesion to the inner wall of the equipment are eliminated, and the problems of insufficient grinding between materials, uneven distribution of raw materials after a large amount of fine grinding, and imbalance in the ratio of chemical elements in the product are improved. The ionic conductivity of the obtained sulfide electrolyte is improved, and the yield is further improved.

[0105] The present application provides a sulfide electrolyte, which is prepared by the method described above.

[0106] In the present application, the general formula of the sulfide electrolyte is (Li A )(G B )(S C )(X D ), wherein 0≤A≤12, 0≤B≤5, 0≤C≤12, 0≤D≤2, and its crystal structure belongs to high- and intermediate-level crystal families (cubic, hexagonal, tetragonal, trigonal systems) or is itself a glass-ceramic phase. The G source includes at least one of P, Ge, Si, Ta, La, Zr, Te, Se, Sn, Sb, etc.; the S source includes at least one of S, O, N, Se, Te, Ge, Si, Ta, La, Zr, Te, Se, Sn, Sb, etc.; the Z source includes at least one of Cl, F, Br, I, OH, O, O2, N, etc.

[0107] The present application provides an all-solid-state battery, which comprises the sulfide electrolyte described above.

[0108] Example

[0109] The present application provides a general and / or specific description of the materials and test methods used in the experiments. In the following examples, unless otherwise specified, % means wt%, i.e., weight percentage. The reagents or instruments used without indicating the manufacturer are all conventional reagent products that can be obtained commercially.

[0110] Example 1 Preparation of sulfide electrolyte

[0111] (1) Li2S, P2S2 and LiCl were put into an electric grinder at a molar ratio of 2.5:0.5:1.0 and ground at a speed of 60 rpm for 20 min. At the same time, an ion blower was used to remove static electricity from the equipment casing to obtain a coarsely crushed powder with a particle size D90 of 3 mm.

[0112] (2) The powder is put into a jet mill with a feed pressure of 0.45 MPa, a grinding pressure of 0.40 MPa, and a grinding gas source of 99.99% argon. An ion blower is used to remove static electricity from the equipment housing, and fine grinding is performed to obtain finely ground powder. The particle size D90 of the finely ground powder is 3 μm. The finely ground powder (i.e., the electrolyte intermediate) is tested by using an electrostatic tester, with the electrode probe head at a distance of 25 mm from the powder. The absolute value of the ion balance of the finely ground powder (i.e., the electrolyte intermediate) is 20 V. CuKα is used for X-ray powder diffraction, and the diffraction pattern is as follows: Figure 1 As shown, from Figure 1 It can be seen that there are characteristic peaks at 30°, 27° and 31.2°. After calculation, the characteristic peak intensity ratio at 30° and 27° is 0.55; the characteristic peak intensity ratio at 30° and 31.2° is 2.49;

[0113] The flowability of the powder was determined using the method of GB / T 1482-2022, which was 40s / 50g;

[0114] The angle of repose of the powder was measured using the method of GB / T 16913-2008, which was 42°;

[0115] The collapse angle was measured using the ASTM D6393-08 method and was 28°

[0116] The difference angle is the difference between the repose angle and the collapse angle, which is 14°.

[0117] (3) The finely ground powder was sintered in a tubular furnace in a 99.99% argon atmosphere at a heating rate of 10°C / min, a sintering temperature of 550°C, a holding time of 2h, and cooled at room temperature to obtain a sulfide electrolyte.

[0118] Example 2 Preparation of sulfide electrolyte

[0119] The difference between Example 2 and Example 1 is that in step (2), no static electricity removal operation is performed to obtain a finely ground sulfide electrolyte (Li6PS5Cl), wherein, for the powder in step (2), the ion balance of the powder is measured in the same manner as in Example 1, and the absolute value of the ion balance of the powder is 40V;

[0120] The measurement was carried out in the same manner as in Example 1. The ratio of the characteristic peak intensity at 30° to 27° was 0.31; the ratio of the characteristic peak intensity at 30° to 31.2° was 1.71;

[0121] The flowability, angle of repose and angle of collapse of the powder were measured in the same manner as in Example 1 and the flowability of the powder was 60s / 50g.

[0122] The repose angle is 38°, the collapse angle is 18°, and the difference angle is 20°.

[0123] Example 3 Preparation of sulfide electrolyte

[0124] The difference between Example 3 and Example 1 is that in step (1), no static electricity removal operation is performed to obtain the sulfide electrolyte (Li6PS5Cl), wherein, for the powder in step (2), the ion balance of the powder is measured in the same manner as in Example 1, and the absolute value of the ion balance of the powder is 30V;

[0125] The flowability, angle of repose and angle of collapse of the powder were measured in the same manner as in Example 1 and the flowability of the powder was 45s / 50g.

[0126] The repose angle is 40°, the collapse angle is 23°, and the difference angle is 17°.

[0127] Example 4 Preparation of sulfide electrolyte

[0128] The difference between Example 4 and Example 1 is that the grinding pressure of the airflow mill is different. The grinding pressure is 0.2 MPa to obtain the sulfide electrolyte (Li6PS5Cl). For the powder in step (2), the ion balance of the powder is measured in the same manner as in Example 1, and the absolute value of the ion balance of the powder is 15 V.

[0129] The measurement was carried out in the same manner as in Example 1. The ratio of the characteristic peak intensity at 30° to 27° was 0.29; the ratio of the characteristic peak intensity at 30° to 31.2° was 1.49;

[0130] The flowability, angle of repose and angle of collapse of the powder were measured in the same manner as in Example 1 and the flowability of the powder was 70s / 50g.

[0131] The repose angle is 38°, the collapse angle is 18°, and the difference angle is 20°.

[0132] Example 5 Preparation of sulfide electrolyte

[0133] The difference between Example 5 and Example 1 is that the sulfide electrolyte (Li 5.5 PS 4.5 Cl 1.5 ), the raw materials used in Example 5 are Li2S, P2S2 and LiCl, and the molar ratio is 2:0.5:1.5, wherein, for the powder in step (2), the ion balance of the powder is measured in the same manner as in Example 1, and the absolute value of the ion balance of the powder is 20V;

[0134] The flowability, angle of repose and angle of collapse of the powder were measured in the same manner as in Example 1 and the flowability of the powder was 34 s / 50 g.

[0135] The repose angle is 43°, the collapse angle is 31°, and the difference angle is 12°.

[0136] Example 6 Preparation of sulfide electrolyte

[0137] The difference between Example 6 and Example 5 is that in step (2), no static electricity removal operation is performed to obtain finely ground sulfide electrolyte (Li 5.5 PS 4.5 Cl 1.5 ), wherein, for the powder in step (2), the ion balance of the powder is measured in the same manner as in Example 1 to obtain an absolute value of 50 V;

[0138] The flowability, angle of repose and angle of collapse of the powder were measured in the same manner as in Example 1, and the flowability of the powder was 62s / 50g;

[0139] The repose angle is 39°, the collapse angle is 20°, and the difference angle is 19°.

[0140] Example 7 Preparation of sulfide electrolyte

[0141] The difference between Example 7 and Example 1 is that the sulfide electrolyte (Li 10 GeP2S 12 ), the raw materials used in Example 7 are Li2S, P2S2 and GeS2, and the molar ratio is 5:1:1, wherein, for the powder in step (2), the ion balance of the powder is measured in the same manner as in Example 1, and the absolute value of the ion balance of the powder is 18V;

[0142] The flowability, angle of repose and angle of collapse of the powder were measured in the same manner as in Example 1 and the flowability of the powder was 38s / 50g.

[0143] The repose angle is 41°, the collapse angle is 25°, and the difference angle is 16°.

[0144] Example 8 Preparation of sulfide electrolyte

[0145] The difference between Example 8 and Example 7 is that in step (2), no static electricity removal operation is performed to obtain the finely ground sulfide electrolyte (Li 10 GeP2S 12 ), for the powder in step (2), the ion balance of the powder is measured in the same manner as in Example 1, and the absolute value of the ion balance of the powder is 31V;

[0146] The flowability, angle of repose and angle of collapse of the powder were measured in the same manner as in Example 1 and the flowability of the powder was 55s / 50g.

[0147] The angle of repose is 37°, the angle of collapse is 17°, and the angle of difference is 20°.

[0148] Comparative Example 1 Preparation of sulfide electrolyte

[0149] Comparative Example 1 is compared with Example 1, and a sulfide electrolyte (Li6PS5Cl) is obtained without performing a static electricity removal operation, wherein, for the powder in step (2), the ion balance of the powder is measured in the same manner as in Example 1, and the absolute value of the ion balance of the powder is 100V;

[0150] The measurement was carried out in the same manner as in Example 1. The ratio of the characteristic peak intensity at 30° to 27° was 0.19; the ratio of the characteristic peak intensity at 30° to 31.2° was 0.94;

[0151] The flowability, angle of repose and angle of collapse of the powder were measured in the same manner as in Example 1 and the flowability of the powder was 80s / 50g.

[0152] The repose angle is 30°, the collapse angle is 8°, and the difference angle is 22°.

[0153] Comparative Example 2 Preparation of sulfide electrolyte

[0154] Comparative Example 2 is compared with Example 1, the difference between which is that no static electricity removal operation is used, no air flow mill is used, and a ball mill (400 rpm, 72 h) is directly used for ball milling to obtain the sulfide electrolyte (Li6PS5Cl), wherein in step (2), the ion balance of the powder is measured in the same manner as in Example 1 to obtain an absolute value of 60 V of the ion balance of the powder;

[0155] The measurement was carried out in the same manner as in Example 1, and no obvious characteristic peaks were found;

[0156] Since the materials are compacted on the inner wall of the ball mill, it is impossible to measure the powder's fluidity, angle of repose and angle of collapse.

[0157] Comparative Example 3 Preparation of sulfide electrolyte

[0158] Comparative Example 3 is compared with Example 1, the difference between which is that a mortar is used for grinding, and a static electricity removal operation is performed during the grinding process to obtain a sulfide electrolyte (Li6PS5Cl), wherein, for the powder in step (2), the ion balance of the powder is measured in the same manner as in Example 1 to obtain an absolute value of the ion balance of the powder of 50V;

[0159] The X-ray diffraction spectrum of the sulfide intermediate was obtained by the same method as in Example 1. Figure 2 As shown, the characteristic peak intensity ratio at 30° and 27° is 0.13; the characteristic peak intensity ratio at 30° and 31.2° is 0.61;

[0160] The flowability, angle of repose and angle of collapse of the powder were measured in the same manner as in Example 1, and the flowability of the powder was 95s / 50g;

[0161] The angle of repose is 28°, the angle of collapse is 9°, and the difference angle is 21°.

[0162] The higher the 27° peak, the worse the grinding effect and the worse the sintering effect. The higher the 30° peak intensity, the better the grinding and sintering effects. The higher the ratio of the characteristic peak intensity at 30° to 27°, the better the grinding and sintering effects. The higher the ratio of the characteristic peak intensity at 30° to 31.2°, the better the grinding and sintering effects.

[0163] Figure 1 is the XRD pattern of Example 1, Figure 2 is the XRD pattern of Comparative Example 3, Figure 2 The 27° peak is Figure 1 To be high, and Figure 1 The 30° characteristic peak in Figure 2 The ratios of the 30° peak intensity to the 27° and 31.2° peak intensity are Figure 1 The spectrum in the figure is higher, indicating that the grinding effect of Example 1 is very good, and the ionic conductivity of the sulfide electrolyte obtained by sintering is higher than that of Figure 2 The ionic conductivity of the sulfide electrolyte obtained by sintering the representative comparative example 3 is much higher.

[0164] Experimental Example 1 Determination of ionic conductivity

[0165] In a room temperature argon environment glove box (O2≤1ppm, H2O≤1ppm), 120mg of the sulfide electrolytes in Examples 1-8 and the sulfide electrolytes obtained in Comparative Examples 1-3 were respectively cold pressed in a cemented carbide mold (370MPa), and the mold diameter was 10mm. The cold-pressed samples were tested in the mold, and an electrochemical workstation (Chenhua CHI660E) was used to perform an AC impedance test (EIS) on the samples, with a test frequency range of 1Hz to 5MHz. After the test, the sample was withdrawn and the thickness of the sample was measured using a spiral micrometer. The room temperature conductivity of the sulfide electrolyte can be calculated from the intercept of the oblique line part of the impedance spectrum on the horizontal axis and the thickness of the sample, and the results are shown in Table 1.

[0166] Table 1 Ionic conductivity improvement ratio

[0167] Ionic conductivity improvement ratio Example 1 1.91 Example 2 1.48 Example 3 1.78 Example 4 1.38 Example 5 1.91 Example 6 1.43 Example 7 1.90 Example 8 1.58 Comparative Example 1 1 Comparative Example 2 1.37 Comparative Example 3 0.48

[0168] It can be seen from Examples 1-8 that step 1 is coarse grinding, in which the static electricity removal step is mainly conducive to the coarse grinding, preventing excessive powder from adhering to the crushing mechanism or the inner wall of the equipment without being crushed, and the obtained product is more uniform and has a smaller particle size, and the yield is also higher, which increases the specific surface area of ​​the particles and facilitates the fine grinding;

[0169] Step 2 is fine grinding, in which the static electricity removal step is mainly conducive to fine grinding. The powder does not adhere to the inner wall of the equipment, and can be fully collided and crushed in the grinding chamber, avoiding accumulation in the grinding chamber and then discharging, resulting in insufficient and uneven material crushing, low yield, imbalance in the raw material ratio, etc., and incomplete static electricity removal will inevitably lead to an imbalance in the element ratio of the material; too much adhesion will inevitably lead to a decrease in yield, and the adhered material will be blown off by high-pressure gas into the powder collection bag, which will cause the incompletely crushed and uneven materials to be mixed into the material;

[0170] Both the coarse and fine grinding processes use a static elimination treatment method, resulting in better overall grinding results, smaller overall particle size, more uniform particle size, higher overall yield, and more uniform material mixing.

[0171] If the crushing pressure is too high (for example, the grinding pressure is 1.0MPa), the raw material crystal form will be destroyed more thoroughly, affecting the sintering effect, and the obtained electrolyte performance will be worse; if the crushing pressure is too low (for example, the grinding pressure is 0.2Mpa), the raw material particle size will be too large, the contact between the particles will be insufficient, and it will also affect the sintering effect, and the obtained electrolyte performance will be poor.

[0172] By comparing the examples with the comparative examples, it can be seen that if the medium-free grinding is not combined with static electricity removal, the raw materials may not be ground sufficiently due to static electricity, resulting in low ionic conductivity of the sulfide electrolyte after sintering.

[0173] Although the ball milling synthesis method can also grind the raw materials into fine powder, since the sulfide electrolyte raw materials are relatively soft, the grinding process will cause them to become compacted and lead to uneven distribution of the raw materials, resulting in different properties of the sintered materials in different places, and the overall conductivity is not high enough.

[0174] In Comparative Example 3, manual grinding was performed using a mortar, and the raw material particles were coarse, the grinding was insufficient, and the contact reaction between them was insufficient, resulting in very low ionic conductivity of the electrolyte obtained after sintering.

[0175] The electrolyte obtained by the method described in the present application has higher ionic conductivity and better synthesis effect. The medium-free grinding and static removal can make the raw materials more fully ground and the raw materials more evenly mixed, which is beneficial to the sintering process and obtains an electrolyte with higher ionic conductivity.

[0176] In summary, the sulfide electrolyte intermediate described in the present application has uniform particle size and material distribution, fine particles, good sintering effect, and uses static electricity removal operation during the preparation process to avoid imbalance in the element ratio of the material, and uses medium-free grinding to avoid damage to the grinding medium itself, thereby reducing the synthesis cost.

[0177] The above is only the preferred embodiment of the present application, and does not limit the present application in other forms. Any technician familiar with the profession may use the above disclosed technical content to change or modify it into an equivalent embodiment with equivalent changes. However, any simple modification, equivalent change and modification made to the above embodiment based on the technical essence of the present application without departing from the technical solution of the present application still falls within the protection scope of the technical solution of the present application.

Claims

1. A method for preparing an intermediate of a sulfide electrolyte, comprising: S1. Mixing and crushing the raw materials to obtain powder; S2. grinding the powder using an inert gas to obtain the intermediate; Here, static electricity is removed in step S1 and / or S2.

2. The method according to claim 1, wherein: The method of fine grinding the powder using an inert gas is to put the powder into a medium-free pulverizer and introduce an inert gas to finely grind the powder to obtain an intermediate.

3. The method according to claim 1, wherein: The medium-free pulverizer is a jet mill or a thin film rotary mixer, preferably a jet mill; preferably, the grinding pressure is 0.1-1.0Mpa, preferably 0.2-0.7Mpa, more preferably 0.2-0.4Mpa.

4. The method according to any one of claims 1 to 3, wherein: After static electricity is removed, the absolute value of the ion equilibrium potential of the powder and the intermediate is less than 100V.

5. An intermediate of a sulfide electrolyte, prepared by the method according to any one of claims 1 to 4.

6. The intermediate according to claim 5, wherein The fluidity of the intermediate is 30s / 50g-75s / 50g; and / or The angle of repose of the intermediate is 50°-31°; and / or The collapse angle of the intermediate is 40°-10°; and / or The difference angle of the intermediate is 8°-20°.

7. The intermediate according to claim 5 or 6, wherein The D50 and / or D90 of the intermediate is 0.1-40 μm.

8. The intermediate according to any one of claims 5 to 7, wherein in the X-ray powder diffraction pattern of the intermediate, the peak intensity relationship between the characteristic absorption peaks is: the characteristic peak intensity ratio at 30°±0.5° and 27°±0.5° is 0.2-1.0; the characteristic peak intensity ratio at 30°±0.5° and 31.2°±0.5° is 1-5, preferably 1.5-3.

9. A method for preparing a sulfide electrolyte, comprising: The intermediate according to any one of claims 5 to 8 is sintered to obtain a sulfide electrolyte.

10. A sulfide electrolyte prepared by the method according to claim 9.